Ship construction - Eyres, David J. (Butterworth-Heinemann, 2012)
Ship Construction is the market leading text for the professional shipbuilding and naval architecture sector. Acting as both a reference on the latest developments in construction techniques, safety and shipyard practice for professionals and a comprehensive text for students of naval architecture, the book covers the complete construction process, from ship specification to competed vessel. Covering each core operation and providing detailed understanding of the key ship construction steps and techniques, this new edition includes the latest developments in computer-aided design and manufacture, plus updated international regulations for ship types, new materials, fabrication technologies, safety practice and shipyard technology. Covers the complete ship construction process including the development of ship types, materials and strengths, welding and cutting and ship structure, with numerous clear line diagrams included for ease of understanding Includes the latest developments in technology and shipyard methods, including a new chapter on computer-aided design and manufacture Essential for students and professionals, particularly those working in shipyards, supervising ship construction, conversion and maintenance.
Keywords: Shipbuilding.; Naval architecture.; elektronické knihy; electronic books